Параметри хімічного складу водних об’єктів та їх вплив на якість води - Кратко, Ольга; Kratko, Olga (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкрито глобальні наслідки антропогенного тиску на довкілля, аналіз стану якості водних об’єктів. Відзначено загострення існуючих проблем із якістю питної води та її вплив на стан здоров’я людини й своєрідний заклик не лише до констатації, а й до дії в інтересах удумливого, ощадливого користування природою, без нанесення їй серйозних травм. У цьому аспекті використовувалися спостереження та дослід- ження санепідемстанції, аналіз доступної новітньої спеціальної літератури. In this review article the global impact of human pressure on the environment, analysis of the quality of water bodies. Reminder reader exacerbation of existing problems of drinking water quality and its impact on human health and the kind of appeal not only to the statement, but also to act in the interests of thoughtful, prudent use of nature, without causing her serious injuries. In this respect, the study used observation and sanitation centers, the latest analysis of the available literature. Environmental assessment of water quality is based on environmental standards – is referring to a class of water, according to environmental category classification based on the analysis of the indicators of its structure and properties. Environmental quality assessment provides information about water as part of the aquatic ecosystem, aquatic living environment and an important part of human environment.
Parameters of the Chemical Composition of Groundwater, and Their Impact on Water Quality
Keywords: хлориди; водойми; очищення; аналіз води; каналізаційні стоки; водні об’єкти; екосистема; пестициди; сульфати; chlorides; water; cleaning; water analysis; sewage; ecosystem; pesticides; sulfates